CD39 Expression identifies terminally exhausted CD8+ T cells - Gupta, P; Godec, J; Wolski, D; Adland, E; Yates, K; Pauken, K; Cosgrove, C; Ledderose, C; Junger, W; Robson, S; Wherry, E; Alter, G; et al. (Public Library of Science, 2015)
Exhausted T cells express multiple co-inhibitory molecules that impair their function and limit immunity to chronic viral infection. Defining novel markers of exhaustion is important both for identifying and potentially reversing T cell exhaustion. Herein, we show that the ectonucleotidse CD39 is a marker of exhausted CD8+ T cells. CD8+ T cells specific for HCV or HIV express high levels of CD39, but those specific for EBV and CMV do not. CD39 expressed by CD8+ T cells in chronic infection is enzymatically active, co-expressed with PD-1, marks cells with a transcriptional signature of T cell exhaustion and correlates with viral load in HIV and HCV. In the mouse model of chronic Lymphocytic Choriomeningitis Virus infection, virus-specific CD8+ T cells contain a population of CD39high CD8+ T cells that is absent in functional memory cells elicited by acute infection. This CD39high CD8+ T cell population is enriched for cells with the phenotypic and functional profile of terminal exhaustion. These findings provide a new marker of T cell exhaustion, and implicate the purinergic pathway in the regulation of T cell exhaustion.